2012
DOI: 10.1016/j.watres.2012.06.023
|View full text |Cite|
|
Sign up to set email alerts
|

Temporal flux and spatial dynamics of nutrients, fecal indicators, and zoonotic pathogens in anaerobic swine manure lagoon water

Abstract: Confined animal feeding operation (CAFO) Clostridium perfringens Escherichia coliCampylobacter Listeria Salmonella a b s t r a c t Confined animal feeding operations (CAFOs) often use anaerobic lagoons for manure treatment. In the USA, swine CAFO lagoon water is used for crop irrigation that is regulated by farm-specific nutrient management plans (NMPs). Implementation of stricter US environmental regulations in 2013 will set soil P limits; impacting land applications of manure and requiring revision of NMPs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 38 publications
(50 reference statements)
2
15
0
Order By: Relevance
“…BOD 5 and COD represented the bacterial mineralization whilst TKN and TP were nutrients for the growth of algae and bacteria and nitrification process. The spatial and temporal variation of these variables in ponds were also reported in previous studies, e.g., McLaughlin et al [24] and Guo et al [25]. Moreover, we modelled the effects of depth and daytime as a logarithm function and a quadratic function, respectively, based on their observed patterns in the studies of Kayombo et al [6] and Tadesse et al [26].…”
Section: Model Selectionmentioning
confidence: 59%
See 2 more Smart Citations
“…BOD 5 and COD represented the bacterial mineralization whilst TKN and TP were nutrients for the growth of algae and bacteria and nitrification process. The spatial and temporal variation of these variables in ponds were also reported in previous studies, e.g., McLaughlin et al [24] and Guo et al [25]. Moreover, we modelled the effects of depth and daytime as a logarithm function and a quadratic function, respectively, based on their observed patterns in the studies of Kayombo et al [6] and Tadesse et al [26].…”
Section: Model Selectionmentioning
confidence: 59%
“…This underestimation can be explained by the sensitivity of mixed models to abnormal observations [40] and the fact that the three sampling campaigns were conducted within one dry season of Ecuador. As the photosynthetic activity of algae changes in response to the seasonal changes in environmental conditions [24,41], there is a need for additional sampling campaigns in the rainy season. From that, the interpolation of this mixed model can be reliably performed within a larger range of observation.…”
Section: Model Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…This was seen for example in anaerobic swine manure lagoon samples in Mississippi, USA, where the rising lagoon water temperature was found to decrease viable Campylobacter counts (McLaughlin et al, 2012).…”
Section: Aerated Lagoonsmentioning
confidence: 94%
“…Westerman et al (2010) also showed decreasing N concentrations in swine lagoons from spring to fall in North Carolina. McLaughlin et al (2012) reported increases of total P and decreases of total N concentrations in swine lagoons in Mississippi from early spring to fall. They reported a dec- rease in the N:P ratio in lagoon water from spring to fall of 71%, while in the present study the TKN:P ratios decreased by 26% to 65%.…”
Section: Seasonal Trends In Physicochemical Characteristics Of Lagoonsmentioning
confidence: 99%